Harris Lines Observed in Trauma: Case Report - Karabağ, Gökmen; Yavuz, Mehmet Sunay; Özdemir, Muhammed Alp; Saraç, Selma; Örgüç, İhsan Şebnem (The Bulletin of Legal Medicine, 2019)
First studies on transverse lines in skeleteon has been done by Dr. Harris in 1931 and they are called as Harris lines. Our study aims to discuss conditions that require attention in evaluation of transverse radiopaque lines which can be observed in bone tissue compatible with trauma. 28-year-old male patient who was injured by motorcycle accident, an abrasion was described in left leg. In examination of radiographs by our department, we observed linear radiopaque appearance on tibia consistent with injury and we consulted to radiology department. When they say this was Harris lines, we prepared a judicial report stating that bone fracture is not occurred due to trauma. In radiographs taken to examine bone lesions in traumatized area, one can encounter with ​​transverse radiopaque lines in bone tissue, compatible with trauma.In cases like this we need to think which can be Harris line and we need to want radiological evaluation.